Implementation of e-learning in learning moral beliefs in 5G class students of the PAI study program majoring in tarbiyah UIN RM Said Surakarta - Nur Zaidi Salim; Supriyanto Supriyanto; M. Nur Yahman (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
This research is a qualitative research with descriptive qualitative techniques. The analysis of research data was obtained from the process of systematic search and preparation, data was obtained from the results of observations, interviews, and the field, namely data collection, data reduction, data presentation, conclusion drawn, and verification. The objectives of this study are: 1) To describe the implementation of E-Learning in Akhidah Akhlak Learning in Class 5G Students of the PAI Study Program, Department of Tarbiyah UIN RM Said Surakarta. 2) to find out the obstacles in the implementation of E-Learning in Moral Learning in Class 5G Students of the PAI Study Program, Department of Tarbiyah, UIN RM Said Surakarta. The results of the study show that the obstacles in the implementation of E-Learning learning are, 1) students do not do assignments on time, 2) students do potluck assignments, 3) passive students when asked by lecturers have difficulty understanding learning, 4) communication with WhatApp class groups that are sometimes ignored and inactive numbers.